ON INTEGRATION OF SEMIOTIC RESEARCH OF SCIENTISTS FROM THE WEST SIBERIAN REGION - Aleksandr I. Kulyapin (Высшее образование в России)
The review of the two journals Discourse and Critics and Semiotics published in Novosibirsk allows to state that the west Siberian Region has become one of the leading centers of the Russian semiotics studies. The establishment of the research and development laboratory on semiotic research of literature and arts in the Ishim Ershov Teachers Training Institute gave the lecturers an opportunity to participate in studying of the actual problems, helped to understand the perspective trends of modern humanitarian science.